ANALYSIS OF QUANTITATIVE VARIATION AND SELECTION CRITERIA FOR YIELD IMPROVEMENT IN EXOTIC GERMPLASM OF UPLAND RICE (ORYZA SATIVA L.) - MOHAN SINGH, CHANDRA; BABU, G. SURESH; KUMAR, BINOD; MEHANDI, SUHEL (The Bioscan, 2013)
The present experiment was conducted with 11 genotypes of upland rice during Kharif 2009 and 2010. Maximum genotypic coefficient of variation (GCV) and phenotypic coefficient of variation (PCV) was observed only for number of spikelets per panicle, while plant height, flag leaf length, flag leaf width, panicle length, harvest index and grain yield per plant showed moderate GCV and PCV. High estimates of heritability coupled with high genetic advance as per cent of mean was observed for plant height, flag leaf length, flag leaf width, number of spikelets per panicle and grain yield per plant. Grain yield showed positive and significant correlation with plant height and panicle length at both genotypic level and phenotypic level. The expected genetic advance and relative efficiency of selection indices was ranged from 0.13 (Index III) – 33.23 per cent (Index XXI) and 4.20 ((Index III) – 1093.09 per cent (Index XXI), respectively. Two genotypes from index XXI and three genotypes from index XVI were isolated as diverse parent with Vandana and can be used in crossing programme to obtain the better heterotic cross combinations with high relative efficiency and good characters combination and may helpful to improve the grain yield in upland rice.